Cheating Or Learning? What Every Student Knows About Open-ai Chatgpt - Ould Si Bouziane, Sabria; Rajaa Adnani, Nour el Imene (The Journal of Studies in Language, Culture, and Society, 2025)
The lines between learning and cheating have become distorted in a world increasingly intertwined with Artificial Intelligence (AI). Experiencing this rapid change within AI affects teachers’ work and how they perceive and assess students’ learning and knowledge. Teachers noticed that many students seized the opportunity to cheat using AI to get good marks on exams and finish writing their dissertations instead of using AI to learn more from their mistakes and enhance their knowledge input. This study seeks to expound on students’ usage and perspectives towards AI by demonstrating whether it is effective in learning or simply used for copying and pasting texts that lead to academic dishonesty. In order to attain this objective, a group of ten supervisees was interviewed on the employment of AI tools in dissertation writing. Therefore, results showed that students considered AI a cheating tool at the beginning and then recognised it as thesis guidance, assistance, and a tool of learning. It is worth noting that AI is deemed a double-edged tool and used halfway between facilitating cheating and learning; thus, balancing its ethical use in education remains critical for everyone’s responsibility.